Popular Press during Fujimori’s Regime: an approach to a reception practice - Torres Vitolas, Miguel Ángel (2015)
Under Fujimori’s regime, Peruvian Press knew the explosion of Popular Press. This one had a very special relationship with Fujimori’s regime and his communication strategies. It could be seen through positive president representations and contenders defamation. Following a semio-pragmatic approach, this article underlines narrative and semantics constants present in media content through this press in their first page and put discursive strategies deployed in relation with reception practices.